2006
DOI: 10.1292/jvms.68.1251
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Rate of Factor XI Deficiency in Stunted Japanese Black Cattle

Abstract: ABSTRACT. Blood examinations and genotyping of Factor XI (F11) were performed in growth retardation Japanese Black cattle and their dams. Genotyping of F11 revealed that the recessive homozygous and heterozygous genotype frequencies were 5.2% and 50.0% in the Claudin-16 (CL-16) deficiency group (n=58), 0% and 14.2% in the renal dysplasia group (n=7), 0% and 26.1% in the non-CL-16 deficiency nephritis group (n=23), 8.9% and 46.7% in the hypogenesis syndrome group (n=45), 6.2% and 25.0% in the neonatal weak calf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
2
5
0
Order By: Relevance
“…These results suggested that cattle with growth retardation were susceptible to infectious disease. Furthermore, this data is consistent with the fact that the GR cattle in this study had contracted WCS with infectious enteritis in their neonatal periods and also with previous reports in which cattle with growth retardation tended to contract WCS [29,30].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results suggested that cattle with growth retardation were susceptible to infectious disease. Furthermore, this data is consistent with the fact that the GR cattle in this study had contracted WCS with infectious enteritis in their neonatal periods and also with previous reports in which cattle with growth retardation tended to contract WCS [29,30].…”
Section: Discussionsupporting
confidence: 93%
“…These cattle do not have any obvious diseases, such as hereditary renal tubular dysplasia or bovine viral diarrhea, and are in good condition with normal appetites and activities [7,8,22,23,26,29,30]. Nevertheless, their body weights and heights are morbidly lower than the criteria of the Japanese Feeding Standard for Beef Cattle [1], even from the juvenile period [22,30].…”
mentioning
confidence: 99%
“…In cattle, the disorder was recorded in the USA as early as 1969 10. Later it was recorded in Canadian11 and British cattle,1 as well as in Holstein and Japanese Black cattle 8, 12, 13…”
Section: Introductionmentioning
confidence: 98%
“…Watanabe et al [11] reported no clinical bleeding tendency in cattle with factor XI deficiency. However, several groups of investigators found that animals affected by factor XI deficiency in Canadian Holstein cattle showed a lower rate of fetal and * CORRESPONDENCE TO: KITAGAWA, H., Department of Veterinary Medicine, Faculty of Applied Biological Sciences, Gifu University, 1-1 Yanagido, Gifu 501-1193, Japan.…”
mentioning
confidence: 96%
“…In Japan, however, there has been no report on its frequency in generally bred Japanese black cattle, though there was one on stunted Japanese black cattle [11]. We investigated the frequencies of the mutant gene in sires and dams of Japanese black cattle.…”
mentioning
confidence: 99%